Self-care of men with priapism and sickle cell disease - Deise Oliveira Costa; Fabíola Azevedo Araújo; Aline Silva Gomes Xavier; Lorena dos Santos Araújo; Ueigla Batista da Silva; Eliene Almeida Santos; Silvia Lúcia Ferreira
ABSTRACT Objective: To identify self-care demands of men with sickle cell disease and priapism and describe self-care measures in light of Orem's Self-Care Theory. Method: This is a descriptive exploratory study with qualitative approach conducted with nine men with a history of sickle cell disease and priapism. Data were analyzed using Orem's Self-Care Theory. Results: Some demands were identified: from universal self-care - difficulty in social interaction and solitude, changes in self-image, self-esteem and sexual activity; from development - the experience with priapism and little knowledge about the pathophysiology of the disease; regarding health deviations - pain crises. Conclusion: Orem's theory allowed to identify self-care demands, which are essential for the nursing care provided for men with priapism. Nursing has an essential role in the measures for the different demands presented.